Calcium-sensing receptor residues with loss- and gain-of-function mutations are located in regions of conformational change and cause signalling bias. (20th July 2018) - Gorvin, Caroline M; Frost, Morten; Malinauskas, Tomas; Cranston, Treena; Boon, Hannah; Siebold, Christian; Jones, E Yvonne; Hannan, Fadil M; Thakker, Rajesh V
Abstract: The calcium-sensing receptor (CaSR) is a homodimeric G-protein-coupled receptor that signals via intracellular calcium (Ca 2+ i ) mobilisation and phosphorylation of extracellular signal-regulated kinase 1/2 (ERK) to regulate extracellular calcium (Ca 2+ e ) homeostasis. The central importance of the CaSR in Ca 2+ e homeostasis has been demonstrated by the identification of loss- or gain-of-function CaSR mutations that lead to familial hypocalciuric hypercalcaemia (FHH) or autosomal dominant hypocalcaemia (ADH), respectively. However, the mechanisms determining whether the CaSR signals via Ca 2+ i or ERK have not been established, and we hypothesised that some CaSR residues, which are the site of both loss- and gain-of-function mutations, may act as molecular switches to direct signalling through these pathways. An analysis of CaSR mutations identified in >300 hypercalcaemic and hypocalcaemic probands revealed five 'disease-switch' residues (Gln27, Asn178, Ser657, Ser820 and Thr828) that are affected by FHH and ADH mutations. Functional expression studies using HEK293 cells showed disease-switch residue mutations to commonly display signalling bias. For example, two FHH-associated mutations (p.Asn178Asp and p.Ser820Ala) impaired Ca 2+ i signalling without altering ERK phosphorylation. In contrast, an ADH-associated p.Ser657Cys mutation uncoupled signalling by leading to increased Ca 2+ i mobilization while decreasing ERK phosphorylation. Structural analysis of these five CaSR disease-switch residues together with four reported disease-switch residues revealed these residues to be located at conformationally active regions of the CaSR such as the extracellular dimer interface and transmembrane domain. Thus, our findings indicate that disease-switch residues are located at sites critical for CaSR activation and play a role in mediating signalling bias